Peranan Imam Maulana Abdul Manaf Amin Al-Khatib (1922-2006) Dalam Pengembangan Pendidikan Islam - Sita Khairiyah; Ahmad Rivauzi (An-Nuha, 2022)
This study aims to find out the role of Imam Maulana Abdul Manaf in the development of Islamic education in Batang Kabung, Padang in the 20th century. The method used in this study is a qualitative method with a socio-historical approach. This research was conducted in the Batang Kabung, Koto Tangah, Tabing Padang. Data collection is done by means of observation, interviews, and documentation. At the data analysis stage, the first thing the writer did was to collect written and oral data sources. Sources of written data are manuscripts by Imam Maulana Abdul Manaf, journals/articles, and related books. While the sources of oral data are direct information obtained from informants. The results of the research show that the development of Islamic education carried out by Imam Maulana Abdul Manaf in Batang Kabung is visible in terms of the education system, initially, the education system in Batang Kabung was a surau education system and was developed into a school education system. The efforts made by Imam Maulana to develop Islamic education in the Batang Kabung, Padang is to build a surau, establish schools, write scripts, and educate.